Transcriptional and Hormonal Responses in Ethephon-Induced Promotion of Femaleness in Pumpkin - Li, Qingfei; Guo, Weili; Chen, Bihua; Pan, Feifei; Yang, Helian; Zhou, Junguo; Wang, Guangyin; Li, Xinzheng (Frontiers in Plant Science, 2021)
The number and proportion of female flowers per plant can directly influence the yield and economic benefits of cucurbit crops. Ethephon is often used to induce female flowers in cucurbits. However, the mechanism through which it affects floral sex differentiation in pumpkin is unknown. We found that application of ethephon on shoot apical meristem of pumpkin at seedling stage significantly increased the number of female flowers and expedited the appearance of the first female flower. These effects were further investigated by transcriptome and hormone analyses of plants sprayed with ethephon. A total of 647 differentially expressed genes (DEGs) were identified, among which 522 were upregulated and 125 were downregulated. GO and KEGG analysis indicated that these genes were mainly enriched in plant hormone signal transduction and 1-aminocyclopropane-1-carboxylate oxidase. The results suggests that ethylene is a trigger for multiple hormone signaling, with approximately 4.2% of the identified DEGs involved in ethylene synthesis and multiple hormone signaling. Moreover, ethephon significantly reduced the levels of jasmonic acid, jasmonoyl-L-isoleucine, and para-topolin riboside but increased the levels of 3-indoleacetamide. Although the level of 1-aminocyclopropanecarboxylic acid was not changed, the expression of ACO genes, which code for the enzyme catalyzing the key rate-limiting step in ethylene production, was significantly upregulated after ethephon treatment. The results indicate that ethephon not only affects the transcription of ethylene synthesis and signaling genes, but also of other hormone signaling genes, especially auxin responsive genes, and modulates the levels of auxin, jasmonic acid, and cytokinin, which may together contribute to femaleness.